Sectoral Labor Supply, Choice Restrictions and Functional Form - John K. Dagsvik; Steinar Strøm (Statistics Norway, Research Department, 2004)
In this paper we discuss a general framework for analyzing labor supply behavior in the presence of complicated budget- and quantity constraints of which some are unobserved. The individual's labor supply decision is viewed as a choice from a set of discrete alternatives (jobs). These jobs are characterized by attributes such as hours of work, sector specific wages and other sector specific aspects of the jobs. We focus in particular on the theoretical justification of functional form assumptions and properties of the random components of the model. The labor supply model for married women is estimated on Norwegian data. Wage elasticities and the outcome of a tax reform analysis show that overall labor supply is moderately elastic, but these modest overall responses shadow for much stronger inter-sectoral changes. Our structural model, with a detailed specification of job opportunities, is compared empirically with a model in which the utility is approximated with a series expansion. It turns out that the performance of our model is at least as good as the labor supply model with flexible preferences.
Keywords: J22; C51; 330; Labor supply; non-convex budget sets; non-pecuniary job-attributes; sector-specific wages.